Prognostic comparison of the proliferation markers mitotic activity index, phosphohistone H3, Ki67, steroid receptors, HER2, high molecular weight cytokeratins and classical prognostic factors in T1-2N0M0 breast cancer - Gudlaugsson, Einar; Klos, Jan; Skaland, Ivar; Janssen, Emiel A.M.; Smaaland, Rune; Feng, Weiwei; Shao, Zhimin; Malpica, Anais; Baak, Jan P.A. (Polish Journal of Pathology, 2013)
The proliferation factors: mitotic activity index (MAI), phosphohistone H3 (PPH3) and Ki67 have strong prognostic value in early breast cancer but their independent value to each other and other prognostic factors has not been evaluated. In 237 T 1-2 N 0 M 0 breast cancers without systemic adjuvant treatment, formalized MAI assessment and strictly standardized, fully automated quantitative immunohistochemistry (IHC) for Ki67, PPH3, estrogen (ER) and progesterone receptor (PR), HER2, cytokeratins-5/6 and -14, and automated digital image analysis (DIA) for measuring PPH3 and Ki67 were performed. Section thickness was measured to further control IHC measurements. All features were measured in the periphery of tumors. The different proliferation assessments and other well-established clinicopathological and biomarker prognostic factors were compared. DIA-Ki67 added prognostically to PPH3. None of the other biomarkers or clinicopathological variables added prognostically to this PPH3/Ki67 combination. However, when PPH3 is replaced by MAI the prognostic value is nearly the same. In early operable node negative breast cancer without adjuvant systemic treatment, Ki67 with a threshold of 6.5% assessed by digital image analysis in the periphery of the tumor is prognostically strong. The combination of either PPH3/Ki67 or MAI/Ki67 overshadowed the prognostic value of all other features including Ki67 alone.